Two models of FX market interventions: The cases of Brazil and Mexico - Martín Tobal; Renato Yslas (Banco de México, 2016)
This paper empirically compares the implications of two distinct models of FX intervention, within the context of Inflation Targeting Regimes. For this purpose, it applies the VAR methodology developed by Kim (2003) to the cases of Mexico and Brazil. Our results can be summarized in three points. First, FX interventions have had a short-lived effect on the exchange rate in both economies. Second, the Brazilian model of FX intervention entails higher inflationary costs and this result cannot be entirely explained by differences in the level of pass-through. Third, each model is associated with a different interaction between exchange rate and interest rate setting (conventional monetary policies).
Keywords: F31; E31; E52; 330; Foreign exchange intervention; Exchange rate pass-through; Exchange rate regime; Monetary policy coordination